The Effect of Capital Expenditure and Regional Original Income (Pad) on Regional Financial Independence with Economic Growth As a Moderating Variable in Regency/City Governments in North Sumatra Province in 2011-2016 - Karimah Arify (ProBisnis : Jurnal Manajemen, 2020)
This study aims to test the Capital Expenditure and Local Revenue (PAD) on the Regional Financial Independence at the Government of Regency / City in North Sumatra Province Year 2011-2016 simultaneously and partially. In addition, this study also aims to determine whether Economic Growth could moderate Capital Expenditure and Local Revenue (PAD) on the Regional Finance Self-Reliance. This type of research is associative research. This research was conducted in Regency and Municipality Government in North Sumatera Province. Samples in this research were 18 regencies / cities in North Sumatra Province period 2011- 2016. Technique Data analysis using Multiple Linear Regression Analysis and Moderating Test. The results showed that: 1. Belanja Capital has a negative and significant effect on the Regional Financial Independence, 2. Local Revenue has a positive and significant impact on the Regional Financial Independence, 3. Result result simultaneously shows that the Capital Expenditure and Revenue Original have a significant effect on Independence Regional Finance, and 4. Economic Growth is a moderating variable between the influence of Capital Expenditure and Local Own Revenue on Regional Financial Independence.